Download presentation
Presentation is loading. Please wait.
Published byGregor Scholz Modified over 9 years ago
1
PolynomdivisionPolynomdivision
2
(x 3 – 3 x 2 – 2 x + 4) : (x – 1) =
3
x3 x3 : x = x2x2 x2x2
4
x 3 : x = x 2 x2x2 x2 x2 · (x–1) = x 3 –x 2 x3 x3 - x2x2
5
(x 3 – 3 x 2 – 2 x + 4) : (x – 1) = x2x2 x 3 - x 2 -2x 2 – 2x
6
(x 3 – 3 x 2 – 2 x + 4) : (x – 1) = x2x2 x 3 - x 2 -2x 2 – 2x -2x 2 : x = -2x - 2x
7
(x 3 – 3 x 2 – 2 x + 4) : (x – 1) = x2x2 x 3 - x 2 -2x 2 – 2x -2x 2 : x = -2x - 2x · (x–1) = -2x 2 +2x -2x 2 + 2x
8
(x 3 – 3 x 2 – 2 x + 4) : (x – 1) = x2x2 x 3 - x 2 -2x 2 – 2x - 2x -2x 2 + 2x -4x + 4
9
(x 3 – 3 x 2 – 2 x + 4) : (x – 1) = x2x2 x 3 - x 2 -2x 2 – 2x - 2x -2x 2 + 2x -4x + 4 -4x : x = -4 - 4
10
(x 3 – 3 x 2 – 2 x + 4) : (x – 1) = x2x2 x 3 - x 2 -2x 2 – 2x - 2x -2x 2 + 2x -4x + 4 -4x : x = -4 -4 · (x–1) = -4x+4 -4x + 4
11
(x 3 – 3 x 2 – 2 x + 4) : (x – 1) = x 2 – 2x - 4 x 3 - x 2 -2x 2 – 2x -2x 2 + 2x -4x + 4 0
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.